Review of the Fund's Strategy on Anti-Money Laundering and Combating the Financing of Terrorism. (Policy Papers; Policy Paper, 2019)
The staff report provides an overview of the Fund's AML/CFT program, since the last review conducted in 2014 and seeks the endorsement of the Executive Board to continue on the basis of the directions given in 2014, with one minor adjustment proposed in relation to Fund-led AML/CFT assessments.